2010
DOI: 10.1016/j.jconrel.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged gene silencing by combining siRNA nanogels and photochemical internalization

Abstract: Small interfering RNAs (siRNAs) show potential for the treatment of a wide variety of pathologies with a known genetic origin through sequence-specific gene silencing. However, siRNAs do not have favorable drug-like properties and need to be packaged into nanoscopic carriers that are designed to guide the siRNA to the cytoplasm of the target cell. In this report biodegradable cationic dextran nanogels are used to deliver siRNA across the intracellular barriers. For the majority of non-viral siRNA carriers stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…The accumulation of nanogel degradation products in the endosomal lumen induced the disruption of the vesicular membrane, possibly through an osmotic effect, thereby released active siRNA into the cytosol. Dex-HEMA-co-TMAEMA nanogel-mediated sustained gene silencing was also achieved by internalization of PS in the nanogel (Raemdonck et al, 2010). For prolonging gene silencing, PS activation was applied at different timepoints after transfecting with siRNA-nanogel on cells.…”
Section: Nanogelmentioning
confidence: 99%
“…The accumulation of nanogel degradation products in the endosomal lumen induced the disruption of the vesicular membrane, possibly through an osmotic effect, thereby released active siRNA into the cytosol. Dex-HEMA-co-TMAEMA nanogel-mediated sustained gene silencing was also achieved by internalization of PS in the nanogel (Raemdonck et al, 2010). For prolonging gene silencing, PS activation was applied at different timepoints after transfecting with siRNA-nanogel on cells.…”
Section: Nanogelmentioning
confidence: 99%
“…This degradation was shown to depend on the crosslink density of the gels (and therefore the degree of substitution of the dex-MA or dex-HEMA). It has also been shown that the crosslink density influences siRNA loading and gene silencing efficacy (60). Although dex-MA gels do not degrade as a function of time, reasonably good transfection efficiency is observed.…”
Section: Discussionmentioning
confidence: 99%
“…Dextran hydroxyethyl methacrylate (dex-HEMA) with a degree of substitution of 5.2 [23] was selected for the preparation of the dextran nanogels based on previous work [24]. Briefly, 150 mg of dex-HEMA was dissolved in a solution containing 97.5 µL irgacure 2959 (10 mg mL -1 in water; Sigma-Aldrich, Bornem, Belgium), 180 µL nuclease-free water and 195 µL of a cationic methacrylate monomer, [2-(methacryloyloxy)-ethyl] trimethylammonium chloride (TMAEMA, 80 wt% solution in water; Sigma-Aldrich).…”
Section: Synthesis Of Dextran Nanogels and Loading With Sirnamentioning
confidence: 99%